(untitled) (The Journal of Plant Protection Sciences, 2020)
Mustard aphid which is influenced by predisposing abiotic factors, has been widely reported as the most noxious insect pest limiting production of rape and mustard. Field experiment was carried out with 3 varieties of rape and mustard, 6 dates of sowing and 2 moisture regimes to understand aphid population dynamics during different phases of growth of rainfed vis-à-vis irrigated rape and mustard crops, and work out relationships between aphid population and weather parameters for its forewarning. Results revealed that initial incidence times of aphid varied from 19 November to 3 December, depending upon dates of sowing done during 1 October to 5 November, which fall under recommended dates of sowing. In crops sown during 22 October to 5 November, critical periods of aphid infestation (having greater than 30 -1 -1 aphids plant ) prevailed between 19 December and 21 January. Number of aphids plant was consistently greater in crops grown under irrigated condition than those under rainfed condition.